miRNA-7a-2-3p Inhibits Neuronal Apoptosis in Oxygen-Glucose Deprivation (OGD) Model - Zhang, Zi-Bin; Tan, Ya-Xin; Zhao, Qiong; Xiong, Liu-Lin; Liu, Jia; Xu, Fei-Fei; Xu, Yang; Bobrovskaya, Larisa; Zhou, Xin-Fu; Wang, Ting-Hua (Frontiers in Neuroscience, 2019)
Neuronal apoptosis is important pathological change in neonatal hypoxic-ischemic brain damage (HIBD), while the role of miR-7a-2-3p in the regulation of HIBD remains to be unknown. The purpose of this study is to explore the mechanism of brain injury and provide theoretical basis for clinical target therapy. Firstly, we established the HI model and verified the model with Zealonga scores and MRI. Next, the changes of miR-7a-2-3p were screened in the ischemic cortex by qRT-PCR at 12h，48h and 96h after HIBD of neonatal rats. Then, we established OGD in pc12 cells, sy5y cells and neurons in vitro. Moreover, qRT-PCR was used to confirm the changes of miR-7a-2-3p in pc12 cells, sy5y cells and neurons with OGD. In order to determine the function of miR-7a-2-3p, pc12 cells, sy5y cells and neurons were used and randomly divided into normal, OGD, mimic-NC, miR-7a-2-3p group, respectively. Then, miR-7a-2-3p mimic transfection was performed and the cortical neurons with Tuj1+ staining, TUNEL staining and MTT were measured, respectively. Lastly, we predicted the target genes of miR-7a-2-3p by prediction database (miRDB, TargetScan, miRWalk and miRmap) and verified the target genes with qRT-PCR in HI rats. HI model and OGD model were successfully established. The expression of miR-7a-2-3p in HI group decreased significantly, compared with the normal group (P<0.01). In functional level, compared with OGD group, the number of pc12 cells, sy5y cells and cortical neurons in miR-7a-2-3p group increased significantly (P<0.01). Meanwhile, the activity of cortical neurons in miR-7a-2-3p group was improved markedly (P<0.01), while the number of neuron apoptosis in miR-7a-2-3p group significantly decreased (P<0.01). Lastly bioinformatics prediction showed that Vimentin (VIM), pleiomorphic adenoma gene 1(PLAG1), dual specificity phosphatase 10 (DUSP10), NAD(P)H dehydrogenase, quinone 1 (NQO1) and tumor necrosis factor receptor superfamily member 1B (TNFRSF1B) might be the targets of miR-7a-2-3p and qRT-PCR confirmed that VIM increased in HI rats (P<0.01). MiR-7a-2-3p played crucial role in hypoxic-ischemic injury, which might be associated with regulation of VIM.